Parcerias público-privadas: a produção capitalista de infraestruturas urbanas na periferia da metrópole brasileira - Thaís Mariano Nassif Salomão (2023)
In this thesis, we propose a critical analysis of Public-Private Partnerships (PPPs) as instruments aimed at urban infrastructure development within a dual periphery context: the outskirts of the Brazilian metropolis, situated on the periphery of global capitalism. More specifically, our focus is on the so-called Administrative and Sponsored Concessions established by the PPP Law in 2004. The central objective of this analysis is to evaluate the potential of these instruments in addressing the national urban infrastructure deficit, particularly concentrated in the outskirts of major Brazilian cities and their metro areas, given the socio-economic, political, and geographical challenges historically faced in infrastructure production within these spaces. The theoretical framework underpinning this analysis draws from the theoretical tradition of political economy, which is of particular relevance for investigations such as this, dealing with transformations in the roles of capital and the state in the production of urban space. Thus, this work commences with a theoretical and historical exploration of the nature, roles, and challenges of urban infrastructure production under capitalism in general, and specifically in the context of Brazilian dependent capitalism. It then proceeds to a historically situated analysis of the legal and financial structure that establishes and supports the operation of the studied PPPs. This is followed by a mapping of the adoption of these instruments across 28 Brazilian urban agglomerations over the nearly two decades since their implementation, paying attention to the spatial, sectoral, and temporal distribution of contracted PPPs, as well as the market conditions of these public contracts. A more in-depth analysis of the adoption and unsuccessful attempts to adopt these instruments at the intra-metropolitan scale is also carried out through the case study of the Belo Horizonte Metropolitan Region. Finally, a deeper dive into the study of public lighting PPPs is conducted with the aim of evaluating the factors influencing the recurrence of these contracts, particularly prevalent at the national level. The results highlight how PPPs technically maneuver around the obstacles posed by neoliberal fiscal austerity measures, reaffirm the central role of the State in urban infrastructure production through risk reduction mechanisms, undermine democratic control in the process of (re)producing these infrastructures, and reinforce investment concentration in regions and sectors already economically sustainable, thereby strengthening rather than reversing the center-periphery distinction that characterizes the national urbanization process.